Bizcocho va a la escuela - Capucilli, Alyssa Satin, 1957-; Schories, Pat; Lombana, Juan Pablo, 1966- (New York : Scholastic, 2012)
A dog follows the bus to school, where he meets the teacher and takes part in the activities of the class.
Originally published in English as Biscuit goes to school.
"This edition is available for distribution only through the school market."--P. [4] of cover.
"Scholastic en espanol"--P. [1] of cover.
Text in Spanish.
Keywords: Biscuit (Fictitious character) -- Juvenile fiction; Dogs -- Juvenile fiction; Puppies -- Juvenile fiction; Schools -- Juvenile fiction; Fiction